Investigation of the effect of copper alloy reinforcement on the physical properties of polymer matrix composite - TAŞDEMİR, MÜNİR (My University, 2022)
Polymer materials are used in many sectors such as automotive, machinery, aviation and medical due to their easy forming, recycling, reuse and strong characteristic properties with their affordable cost. The properties of polymer materials such as thermal, mechanical and electrical conductivity can be improved by using these materials as polymer-metal, polymer-polymer, polymer-fiber composites. This makes polymer composites the preferred material for many specific applications. In this study, PE and PP were used as matrix materials. Reinforced copper alloy CuCrZr powder particles were added at a rate of 0.5%- 1%-3%-5% by weight. The materials were granulated using a twin screw extruder. Then, test coupons were printed with an injection machine. Molded samples; melt flow index, moisture absorption, thermal distortion temperature, vicat softening temperature, wear rate, static and dynamic friction coefficient and scanning electron microscopy (SEM) tests were carried out. The results of the tests were examined and the effects of copper powder supplementation on polyethylene and polypropylene were investigated. According to the results of the tests, it was determined that with the increase of copper powder ratio in the matrix, the moisture absorption value decreased, while the thermal distortion temperature, vicat softening temperature, melt flow index, friction coefficient and wear rate values increased
Keywords: PE; PP; Copper Powder; Metal Powder; Polymer composite; Physical Properties.